Comparison studies for the removal of a basic dye from aqueous solution using coffee residues and waste tea - Benhachem, Fatima-Zahra; Attar, Tarik (International Journal of Advanced Chemistry, 2019)
Dyes are one of the most important industrial pollutants, especially in textile industries. The coffee residues and wastes tea are food industrial solid wastes, were used as low-cost adsorbents for the removal of methylene blue (MB) dye from aqueous solution. Many methods have been proposed in order to remove color from wastewater among which, adsorption is more acceptable due to the ability for its use in the large scale. The influence of various experimental factors such as contact time, adsorbent dosage, temperature and pH of dye solution was investigated. Two simplified kinetic models including pseudo-first-order and pseudo-second-order equation were selected to follow the adsorption processes. It was observed that chemisorptions pseudo-second order kinetic model described the sorption process with high coefficients of determination (R2) better than pseudo-first order kinetic model. Thermodynamic parameters such as ΔG°, ΔH°, and ΔS° were calculated the results of this parameteres indicated that the adsorption of methylene blue onto residues coffee and waste tea were spontaneous process.